Asymmetric Four-Terminal Solar Concentrator Improving Power Collection in Bifacial Solar Cells - Floriana Morabito; Daniela Fontani; Paola Sansoni; Salvatore Lombardo; Andrea Farina; Silvia Maria Pietralunga (Energies)
The exploitation of bifacial solar cells in photovoltaics aims to provide cost-effective solutions to maximize solar power collection on specific surfaces. A prerequisite for this is the effective collection of backscattered diffuse light from albedo, to which self-shading is an obstacle. We discuss the benefits of bifaciality for an asymmetric low-concentrating and spectral-splitting photovoltaic optics system that features a wedged right-prism geometry to address self-shading. The performance of the conceptual design is analyzed, using commercial ray-tracing software, for four different latitudes of installation, by assuming a standard solar AM1.5G spectrum as input. The daily Relative Optical Power Increase (ROPI) is evaluated with respect to standard flat bifacial configurations, reaching ROPI = 293% at a latitude of 25° north at winter solstice. The photocurrent and total Power Conversion Efficiency (PCE) in a four-terminal (4T) configuration are estimated, assuming the operation of a commercial Si HJT bifacial cell and a commercial single-junction GaAs cell. A global increase in PCE of up to 23% is obtained with respect to the best-performing trackless standard bifacial configuration. From this perspective, the use of high-performance, high-bandgap solar cells in 4T configurations might further leverage the advantages of the optics proposed here.